Manipulating Electrocatalysis using Mosaic Catalysts. Issue 5 (27th March 2021) - Luo, Yuting; Chiang, Sum Wai; Tang, Lei; Zhang, Zhiyuan; Yang, Fengning; Yu, Qiangmin; Ding, Baofu; Liu, Bilu
Abstract : Understanding the mechanisms and developing strategies toward efficient electrocatalysis at gas–liquid–solid interfaces are important yet challenging. In the past decades, researchers have devoted many efforts to improve catalyst activity by modulating electronic properties of catalysts in terms of chemical components and physical features. Herein, a mosaic catalyst, which is defined as a catalyst with spatially isolated and periodically distributed active areas, is developed to dramatically improve the activity of catalysts. Taking Pt catalyst as an example, the mosaic Pt leads to high catalytic performance, showing a specific activity 11 times higher than that of uniform Pt films for hydrogen evolution reaction (HER), as well as higher current densities than commercial Pt/C and uniform Pt films. Such a strategy is found to be general to other catalysts (e.g., 2D PtS) and other reactions (e.g., oxygen evolution reaction). The improved catalytic performance of the mosaic catalysts is attributed to enhanced mass transferability and local electric field strength, both of which are determined by the occupation ratios of catalysts. The work shines new light on manipulating electrocatalysis from the perspective of the spatial structures of catalysts, which guides the design of efficient catalysts for heterogeneous reactions. Abstract : Developing strategies toward efficient electrocatalysis is crucial to chemical production and energy conversion systems. Instead of focusing on the chemical component and nanostructure of catalysts, a mosaic catalyst strategy is developed to improve the activity of electrocatalysts by engineering their spatial structures, which is another degree of freedom to modulate the performance of catalysts.